Criteria of vital activity lesions as a methodological basis for determining disability. - L. Naumenko; I. Borisova; V. Berezovskyi; H. Fesenko; T. Zub; D. Chub (Medičnì Perspektivi)
Evaluation of the functional state of the patient is the basis for recognizing him persistently incapacitated. The reform in the field of medicine in our country entrusts the function of the initial selection of such patients to general practitioners and primary care physicians. In 2001, the working group of the World Health Organization approved the International Classification of Functioning, Disability and Health. There are 7 basic parameters for detailing the functioning of a person: the ability to self-service, to move, to work, to orientate, to control own behavior, to learn, to communicate. The ability to self-service characterizes a person's capability to provide own physiological needs, to adhere to own hygiene and to perform daily activities. A person with a preserved capacity for self-service does not depend on other people.The ability to move allows the person to move in space independently: to walk, to run, to overpass the obstacles, to use public transport. If this criterion is limited, the person needs more time to overcome the distance or uses the additional support or needs help from outside. The ability to orient allows the person to analyze the surrounding world with the help of eyes and ears.The ability to communicate provides an opportunity to establish contacts and maintain relationships with other people. For communication spoken, written and non-verbal speech is used. The ability to control one's own behavior consists in the awareness of one's own personality and one's own place in the world, limited by certain norms and rules of behavior. The ability to learn allows the person to perceive, comprehend, accumulate and reproduce the information. Due to this,the person can accumulate knowledge and skills. Ability to work allows the person to perform work according to the level of one’s own education. The definition of criteria for disability and the degree of their severity requires a certain level of medical training for general practitioners and primary care physicians.